Desarrollo de un videojuego en realidad virtual implementando metodologías ágiles en conjunto con una empresa (2017)
This degree project allows to evaluate the ability to develop, manage and implement an engineering project, which is why two students worked together with the company 12 Hit Combo developing a video game of third person puzzle type in virtual reality (VR ) (Games, sf) using the Unreal Engine 4 platform (UE4). The game was developed with SCRUM methodology with incremental sprints of short duration of one week and its revision through follow-up meetings with the teacher in charge, Pablo Figueroa, in which all the documents related to the progress of the project were presented.--Tomado del Formato de Documento de Grado.